Irrationally elliptic closed characteristics on symmetric compact convex hypersurfaces in R^8 - Wang, Wei (Topological Methods in Nonlinear Analysis, 2023)
Let $Σ$ be a $C^3$ compact symmetric convex hypersurface in$\mathbb{R}^{8}$. We prove that when $Σ$ carries exactly fourgeometrically distinct closed characteristics, then there are at least twoirrationally elliptic closed characteristics on $Σ$.